The ethical student scale: Development of a new measure - Tuvana Rua; Leanna Lawter; Jeanine Andreassi (Organization Management Journal (OMJ), 2024)
Purpose - The purpose of this study is to develop the "ethical student scale" to understand the underlying factors that lead to the decisions of cheating and plagiarism and where business students are developmentally from a moral perspective and to help academic institutions assess how best to develop ethical education throughout the curriculum. This three-dimensional nine-item scale based on Kohlberg's moral development model is proposed to serve as a valuable tool for educators who are struggling with identifying the best approach to help their students make ethical choices both within and outside of the walls of their educational institutions and once they join the workforce. Design/methodology/approach - Four survey design studies were conducted to determine what factors had previously been identified to both negatively and positively impact the propensity of a university student to engage in cheating and/or plagiarizing (Study 1, N = 179), to preliminarily validate the three dimension nine item scale that emerged from Study 1 (Study 2, N = 87); to test the construct validity of the three-dimensional nine-item scale (Study 3, N = 235); and to test the nine-item scale for convergent, divergent and predictive validity (Study 4, N = 201). The four surveys were administered to undergraduate students at two universities in the Northeast in the USA. Findings - To shed light on the underlying factors that lead to the decisions of cheating and plagiarism, the authors propose three factors that are engaged when students make these types of ethical decisions: rules and enforcement as an external control, personal morality as an internal control and social influences as a social control (Kohlberg, 1976). Through four studies, this paper presents a three-dimensional nine-item scale based on Kohlberg's moral development model to determine the factors that influence the propensity of a university student to engage in cheating and/or plagiarizing. The proposed scale showed strong reliability across the three dimensions. Research limitations/implications - The limitations of the scale are that this research was restricted to an academic setting. The relationship between the academic environment, the resulting behaviors of students and the subsequent behavior of these students as managers also needs investigation to determine if business ethics education does have an impact on increasing ethical decision-making. Practical implications - The ethical student scale attempts to measure the development stage of students in a university setting and has the potential utility to help higher education institutions better understand the moral development of their students and what drives their decisions to engage in an ethical manner. Being a short yet reliable tool, ethical student scale may help business schools develop programs beyond a single business ethics course to instill ethical decision-making in students. Social implications - One of the goals as business educators is to produce ethical managers. The ethical student scale can help us develop a more integrated approach to business ethics education. As the students become managers and leaders in organizations, the social implications for more ethical decision-makers and organizations are widespread and vital to the community and the economy. Originality/value - Ethical student scale is an attempt to quantify what types of controls (external, social, or personal) help develop ethical students and ethical managers. Based on Kohlberg's moral development model, this three-dimensional nine-item scale which shows strong reliability will serve as a valuable tool for educators who are struggling with identifying the best approach to the issue of unethical decisions and behaviors as they try to create strategies to help their students make ethical choices both within and outside of the walls of their educational institutions and once they join the workforce.
Keywords: 650; Academic dishonesty; Ethical decision-making; Ethics; Ethics scale; Kohlberg